Pelatihan Kemampuan Guru MI Nurul Falah Bojonggede Bogor dalam Menyajikan Presentasi dengan Microsoft Power Point - Tantowi, Akhmad Aris; Birowo, Achmad; Surachman, Arie (Jurnal PKM: Pengabdian Kepada Masyarakat, 2024)
Advances in information and communication technology have had a significant impact on the world of education. One tool that is often used in learning is Microsoft PowerPoint. Attractive presentations via Microsoft PowerPoint can increase the attractiveness and effectiveness of teaching in the classroom. By utilizing learning media in the form of Microsoft Power Point, the learning process is felt to be easier for teachers and more attractive for students in participating in learning, because it is presented in a more interesting and creative form. This research aims to investigate and improve the ability of MI Nurul Falah teachers in presenting attractive presentations using Microsoft PowerPoint media in Bojong Gede, Bogor Regency, West Java.